Supply Logistics and Operations Management: A Case Study in an Agroindustrial Company in Trujillo - Peru (LACCEI, 2024)
The research entitled "Supply logistics and operations management of Maygon de Trujillo, 2022" to obtain the professional title of Bachelor of Administration from the Antenor Orrego Private University, had as a general objective to determine the relationship that exists between supply logistics and the operations management of the company Maygon de Trujillo, in the year 2022. The type of correlational study and the non- experimental research design were used, a study was carried out through observation and compilation at 60 days (two months May and June) being this our sample and population studied, using a data collection tool such as the observation sheet, which was used from the first moment of the information. This instrument was validated through the IBM SPSS Statistics v25 program. In addition, using the Pearson correlation coefficient (0.386 -.0.816 – 0.655 – 0.973 – 0.619 – 0.653 – 0.027 – 0.027 – 0.012) it was determined that there is no correlation between both variables In the same way, the indicators of the operations management were evaluated, so we can say that they are being handled correctly and that only in the stock of merchandise, you have to be a little careful on the other hand, the indicators of operations management were also evaluated, in this I can only say that the company fulfilling its strategies and objectives, in order to grow correctly in a market that is competitive Finally, the relationship between the supply logistics indicators and the operations management indicators of the company Maygon de Trujillo, 2022, was determined, using the correlation coefficient with a significance of 0.386 - 0.816 - 0.655 - 0.973 - 0.619 - 0.653 – 0.027 – 0.027 – 0.012 for number of orders to suppliers, merchandise stock, inventory turnover (production volume, efficiency and effectiveness) concluding that there is no relationship between the first 6 indicators, therefore the variables are not related compared to the last 3 indicators that are related and therefore the two study variables.